2011
DOI: 10.1002/jssc.201100394
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dextran layer on protein uptake to dextran‐grafted adsorbents for ion‐exchange and mixed‐mode chromatography

Abstract: In the current research, a series of dextran-grafted adsorbents were prepared using sulfopropyl and 4-(1H-imidazol-1-yl) aniline as chromatographic ligands for ion-exchange (IEC) and mixed-mode chromatography (MMC) to respectively investigate the influence of dextran layer on adsorption of γ-globulin. Experimental evidences of static adsorption on dextran-grafted IEC adsorbents showed that adsorption capacity of γ-globulin increased with dextran content. It could be attributed to the multilayer adsorption of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 51 publications
5
34
0
Order By: Relevance
“…of uptake rate is mainly attributed to the decreased "adsorptioncaused hindrance" from the adsorbed BSA molecule to the free BSA molecule, as the adsorption capacity decreased with increasing butyl density. Additionally, that the severer collapse of the PEI layer with increasing hydrophobic groups (Yu et al, 2011) enlarged the pore size and then decreased the diffusion hindrance (Liu et al, 2014a;) also contributed.…”
Section: Protein Batch Uptakementioning
confidence: 96%
See 3 more Smart Citations
“…of uptake rate is mainly attributed to the decreased "adsorptioncaused hindrance" from the adsorbed BSA molecule to the free BSA molecule, as the adsorption capacity decreased with increasing butyl density. Additionally, that the severer collapse of the PEI layer with increasing hydrophobic groups (Yu et al, 2011) enlarged the pore size and then decreased the diffusion hindrance (Liu et al, 2014a;) also contributed.…”
Section: Protein Batch Uptakementioning
confidence: 96%
“…Static adsorption experiments of BSA and γ-globulin were carried out at 0 or 1.0 mol/L NaCl in 20 mmol/L Tris-HCl (pH 8.0) with the method reported previously (Yu et al, 2011). The Langmuir model was used to describe the adsorption isotherms,…”
Section: Adsorption Isotherms and Kineticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further evidence of protein adsorption in poly(ethylenimine) (PEI)-grafted Sepharose FF reported by Yu et al demonstrated that there was a critical ionic capacity or PEI chain density above which the protein adsorption capacity and effective diffusivity increased sharply [14]. However, the intrinsically heterogeneous architecture of these ion-exchange beads caused by the distribution of the added polymer and ligand leads to a tendency to complicate and intensify mechanistic and synthetic issues of chromatography, which must be addressed [11,15].…”
Section: Introductionmentioning
confidence: 94%